Biological sample collections from minors for genetic research: a systematic review of guidelines and position papers - Hens, Kristien (Nature Publishing Group, 2009)
Stored tissue samples are an important resource for epidemiological genetic research. Genetic research on biological material from minors can yield valuable information on the development and genesis of early-onset genetic disorders and the early interaction of environmental and genetic factors. The use of such tissue raises some specific ethical and governance questions, which are not completely covered by the discussion on biological materials from adults. We have retrieved 29 guidelines and position papers pertaining to the storage and use of biological tissue samples for genetic research, originating from 27 different organizations. Five documents have an international scope, three have an European scope and 21 have a national scope. We discovered that 11 of these documents did not contain a section on biological materials from minors. The content of the remaining 18 documents was categorized according to four themes: consent, principles of non-therapeutic research on vulnerable populations, ethics committee approval and difference between anonymous and identifiable samples. We found out that these themes are not consistently mentioned by each document, but that documents discussing the same themes were mostly in agreement with their recommendations. However, a systematic reflection on the ethical and policy issues arising from the participation of minors in biobank research is missing.